(untitled) (Research, Society and Development, 2021)
The aim of this study was to evaluate the presence of contents related to dental caries in textbooks of public elementary schools I (1st to 5th grade) and II (6th to 9th grade). The descriptive documentary study with a quantitative approach used a standardized form developed for the study to evaluate the content of the textbooks of first choice of Sciences in 30 schools in the city of Vitória-ES, Brazil. 130 books were made available, 10 for each year of Elementary School I and 20 for each year of Elementary School II. After removing the duplicates, 29 titles were analyzed. A total of 11 books (37.9%) addressed the content of dental caries, and are available only for the 1st (n = 1), 2nd (n = 2), 4th (n = 1), 5th (n = 3) and 8th (n = 4) school years. Of the books that deal with dental caries content, the most discussed content in the books were the role of bacteria in the appearance of caries (81.8%) and encouraging hygiene practices (72.7%), and the least frequent was the role fluoride in the prevention of caries (18.2%) and the aspect of restorative caries treatment (18.2%). There was greater diversification of content in books from 2 years (66.7%) and 8 years (100.0%) of the 6 contents evaluated. And in general the contents were more complete in the books of the 8th year. It is concluded that the theme of dental caries is addressed in less than half of the science textbooks, more present in elementary school I and more complete in elementary school II.